2024
DOI: 10.1152/ajprenal.00247.2023
|View full text |Cite
|
Sign up to set email alerts
|

Current perspective on circadian function of the kidney

Jazmine I. Benjamin,
David M. Pollock

Abstract: Behavior and function of living systems are synchronized by the 24-hour rotation of the earth that guides physiology according to time of day. However, when behavior becomes misaligned from the light/dark cycle, such as in rotating shift work, jet lag, and even unusual eating patterns, adverse health consequences such as cardiovascular or cardiometabolic disease can arise. The discovery of cell autonomous molecular clocks expanded interest in regulatory systems that control circadian physiology including withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 268 publications
0
1
0
Order By: Relevance
“… 5 The kidneys also have a profound circadian rhythm. 6 Studies have shown that renal injury and cardiovascular dysfunction are present when any of the core regulating genes for circadian rhythm are knocked out. 7 Also, a study on mice showed that coronary ischemia reperfusion injury was more severe during the sleep-to-wake transition than during the wake-to-sleep transition.…”
mentioning
confidence: 99%
“… 5 The kidneys also have a profound circadian rhythm. 6 Studies have shown that renal injury and cardiovascular dysfunction are present when any of the core regulating genes for circadian rhythm are knocked out. 7 Also, a study on mice showed that coronary ischemia reperfusion injury was more severe during the sleep-to-wake transition than during the wake-to-sleep transition.…”
mentioning
confidence: 99%